2023
DOI: 10.3390/polym15061587
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Heat Treatment on a 3D-Printed PLA Polymer’s Mechanical Properties

Abstract: Three-dimensional printing is a useful and common process in additive manufacturing nowadays. The advantage of additive polymer technology is its rapidity and design freedom. Polymer materials’ mechanical properties depend on the process parameters and the chemical composition of the polymer used. Mechanical properties are very important in product applicability. The mechanical properties of polymers can be enhanced by heat treatment. Additive-manufactured PLA’s mechanical properties and structure can be modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 32 publications
(44 reference statements)
7
10
0
Order By: Relevance
“…Following the variation graphs shown above, it can be considered that the values obtained for hardness are opposite to those for tensile strength. Comparing the results obtained with those found in the literature, it is found that they fall within the range of 79–84 HD, values also obtained by other researchers [ 26 , 31 ], raising the degree of confidence in the accuracy of the values obtained in this study.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Following the variation graphs shown above, it can be considered that the values obtained for hardness are opposite to those for tensile strength. Comparing the results obtained with those found in the literature, it is found that they fall within the range of 79–84 HD, values also obtained by other researchers [ 26 , 31 ], raising the degree of confidence in the accuracy of the values obtained in this study.…”
Section: Resultssupporting
confidence: 88%
“…The experimental values and trends are in agreement with the results obtained by other researchers in the literature [ 18 , 31 , 32 , 47 , 48 ]. This convergence of results from multiple sources significantly bolsters the confidence level associated with the outcomes presented in this paper, further confirms the possibility of applying in-process annealing during additive manufacturing, and also strengthens the reliability and significance of the multiple research studies from the literature.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The other solution to improve the quality of the mechanical properties of the FDM components is annealing [27][28][29]. This is a post-process that includes heating the material to a high temperature above its glass transition temperature to enhance the chains' molecular mobility in the structure and keeping it at this temperature for a specific time resulting in amplifying interlayer bonding [30].…”
Section: Introductionmentioning
confidence: 99%
“…Shbanah et al studied the effect of heat treatment (annealing) on the mechanical properties and structure of PLA. They heat-treated the printed specimens at 55 °C, 65 °C and 80 °C for 5 h and then keeping them at 20 °C for 15 h. The results of their work show that the optimal heat treatment was 65 °C for 5 h and also presented a 35% increase in the tensile strength of the material and a decrease in the amount of porosity in the structure [27].…”
Section: Introductionmentioning
confidence: 99%